Mepolizumab to prevent exacerbations of COPD with an eosinophilic phenotype - Sciurba, Frank; Criner, Gerard J.; Christenson, Stephanie A.; Martinez, Fernando J.; Papi, Alberto; Roche, Nicolas; Bourbeau, Jean; Korn, Stephanie; Bafadhel, Mona; Han, MeiLan K.; Kolterer, Stefanie; Miller, Karen; et al. (The New England journal of medicine, 2025)
BACKGROUND Mepolizumab is a humanized monoclonal antibody that targets interleukin-5, a cytokine that plays a central role in eosinophilic inflammation, which is present in 20 to 40% of patients with chronic obstructive pulmonary disease (COPD). - METHODS In a phase 3, double-blind, randomized, placebo-controlled trial, patients with COPD, a history of exacerbations, and a blood eosinophil count of at least 300 cells per microliter who were receiving triple inhaled therapy were assigned, in a 1:1 ratio, to receive mepolizumab (at a dose of 100 mg) or placebo subcutaneously every 4 weeks for 52 to 104 weeks. The primary end point was the annualized rate of moderate or severe exacerbations. Secondary end points, tested hierarchically to control for multiplicity, were moderate or severe exacerbation as assessed in a time-to-first-event analysis, measures of health-related quality of life and symptoms, and the annualized rate of exacerbations leading to an emergency department visit, hospitalization, or both. - RESULTS Of the 804 patients who underwent randomization, 403 were assigned to receive mepolizumab and 401 to receive placebo. The annualized rate of moderate or severe exacerbations was significantly lower with mepolizumab than with placebo (0.80 vs. 1.01 events per year; rate ratio, 0.79; 95% confidence interval [CI], 0.66 to 0.94; P = 0.01). The time to the first moderate or severe exacerbation was longer with mepolizumab than with placebo (Kaplan-Meier median time to the first moderate or severe exacerbation, 419 vs. 321 days; hazard ratio, 0.77; 95% CI, 0.64 to 0.93; P = 0.009). Between-group differences in measures of health-related quality of life and symptoms were not significant; thus, no statistical inferences regarding subsequent secondary end points in the statistical testing hierarchy were made. The incidence of adverse events was similar in the mepolizumab and placebo groups. - CONCLUSIONS Treatment with mepolizumab led to a lower annualized rate of moderate or severe exacerbations when added to background triple inhaled therapy among patients with COPD and an eosinophilic phenotype. (Funded by GSK; MATINEE ClinicalTrials.gov number, NCT04133909.)
Gesehen am 27.10.2025